SISTEM PENGUKURAN DAN PEMUTUSAN PENGGUNAAN DAYA LISTRIK SECARA REAL TIME BERBASIS INTERNET OF THINGS - Aliza Cahyo Putranto; Muhammad Yaser (TESLA: Jurnal Teknik Elektro, 2022)
During the Corona Virus Diseases-19 (COVID-19) pandemic, the recording of kilo Watt hours (kWh) meters was not carried out in every home due to Work from Home (WFH). The calculation of the electricity bill for consumers whose kWh meter is not recorded is done by averaging the electricity usage for the previous three months. Increased activity at home also increases household electricity consumption. Supervision of the use of electric power by customers is needed as transparency in the use of electric power. Therefore, in this study, a real-time internet of things-based disconnection and measurement system for electric power usage was designed. In this design, limiting the maximum electrical power can be done by the NodeMCU which controls the Solid-State Relay (SSR) as a switch, the NodeMCU can communicate with the internet so that officers do not need to visit the customer's house to change the electrical power. The system of changing electrical power and measuring electrical power can be monitored throughout Indonesia with an internet connection from the NodeMCU to the customer. The PZEM-004T sensor can detect the current flowing in the mains and also the AC voltage which can be used as a measurement of electrical power by the NodeMCU. The web design is made so that customers can see the amount of electricity bills running in real time. the power factor in the design of the constant device is 0.8 or 20 percent lower than the power factor used in the Itron kWh meter. So, there is a 20% margin between the power on the tool and the kWh meter. The cut-off test was successful for 450W and 900W maximum power ABSTRAK:Selama pandemi Corona Virus Diseases-19 (COVID-19) pencatatan kilo Watt hours (kWh) meter tidak dilakukan di setiap rumah karena Work from Home (WFH). Perhitungan tagihan listrik bagi konsumen yang tidak tercatat kWh meternya dilakukan dengan cara merata-ratakan penggunaan listrik tiga bulan sebelumnya. Peningkatan aktifitas di rumah juga meningkatkan konsumsi listrik rumah tangga. Pengawasan penggunaan daya listrik oleh pelaggan diperlukan sebagai transparansi penggunaan daya listrik. Oleh karena itu pada studi ini dirancang sistem pemutusan dan pengukuran penggunaan daya listrik secara realtime berbasis internet of things. Pada perancangan ini, pembatasan daya maksimum listrik dapat dilakukan NodeMCU yang mengendalikan Solid State Relay (SSR) sebagai saklar, NodeMCU dapat berkomunikasi dengan internet sehingga petugas tidak perlu mengunjungi rumah pelanggan untuk merubah daya listrik. Sistem perubahan daya listrik dan pengukuran daya listrik dapat di pantau di seluruh Indonesia dengan koneksi internet dari NodeMCU ke pelanggan. Sensor PZEM-004T dapat mendeteksi arus yang mengalir pada listrik dan juga tegangan listrik AC yang dapat digunakan sebagai pengukuran daya listrik oleh NodeMCU. Perancangan web dibuat agar pelanggan dapat melihat jumlah tagihan listrik yang berjalan secara real time. faktor daya pada perancangan alat konstan yaitu 0,8 atau 20 persen lebih rendah dibandingkan faktor daya yang digunakan pada kWh meter Itron. Sehingga terdapat margin 20% antara daya pada alat dan kWh meter. Pengujian pemutusan daya berhasil dilakukan untuk daya maksimum 450W dan 900W.